A produç\~ao agropecuária e o arcabouço jurídico para o fomento das ferrovias no Brasil - Thaís Araripe Dias; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This paper analyzed the Brazilian agribusiness scenario, highlighting its progress and the infrastructure difficulties. In this context, railways emerge as a promising solution, especially with the new legal regulatory frameworks. A detailed analysis of railway legislation suggests that the private sector could share more in the construction of projects, assuming its own risk. This contribution is essential to overcome infrastructural bottlenecks and, at the same time, reduce dependence on the public budget. This alignment between agribusiness development and advancements in the railway sector results in significant reductions in the country's operational costs. As a result, railways promote a more favorable economic scenario, as well as represent a sustainable alternative for national development.
Keywords: Q13; R42; R58; O13; 330; agribusiness; growth; infrastructure; railways